Third Argentine record of Eurhopalotrhix bruchi (Santschi, 1922) (Hymenoptera, Formicidae), description of an interomorphic queen and the colony, and notes on biology and ecology - Arcusa, Juan Manuel (2018)
Eurhopalothrix bruchi is the only species of the genus present in Argentina. We present only the third record of this species from Argentina and describe for the first time the female and characteristics of the colony. The nest collected had 48 workers, 6 queens, and 4 pupae. The queens are characterized as wingless, without wing sclerites, and worker-like. The scarcity of pre-imaginal stages suggests that fission of the colony led to the nest?s foundation.